Combined Application of Singing Method and Flash Card Media for Students’ Mastery of Arabic Vocabulary - Syaripah, Euis Siti; Nursyamsiah, Nunung; Maulani, Hikmah (Postgraduate of IAIN Metro Lampung Indonesia, 2024)
Singing is one of the learning methods that aims to help students master the material well. In addition to methods, media is also very important to improve the mastery of students’ memory. One of them is flash card media. Flash card media which is a card containing images, text, or symbols that remind or guide students to something related to the image. At QEC Asy-Syukuriyah using flash cards that measure 8 x 12 cm, because flash cards usually measure 8 x 12 cm or can be adjusted to the size of the class faced by the educator. With the combination of the use of singing methods and flash card media, making the learning process more interesting and further stimulating students mastery of Arabic mufradat material. Based on initial observations, the lack of mastery of students of Arabic vocabulary material at QEC Asy-Syukuriyah Bandung City, the efforts made are to apply a combination of singing methods and flash card media. This research uses qualitative research methods. The data collection techniques were interviews, documentation studies and observations. The data analysis technique carried out by researchers is descriptive qualitative data analysis technique. The results of this study indicate that with the combined application of singing method and flash card media in mastering the Arabic vocabulary of students has increased significantly, because it is proven that students can master Arabic vocabulary well, one of which is through Arabic language material about fingers using flash cards and accompanied by the song Heli Guk Guk Guk.song Heli Guk Guk Guk.